2020
DOI: 10.3390/su12051944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8-Weeks Concurrent Strength and Aerobic Training on Body Composition, Physiological and Cognitive Performance in Older Adult Women

Abstract: (1) Background: Despite plenty of evidence supporting the advantages of regular physical exercise amongst older women, it is not clear what the best methodology is to improve these parameters. Considering the growth of older population and aging process, this study analyses an 8-weeks concurrent training intervention; (2) Methods: A total of 48 older women participated in concurrent strength and aerobic exercises training intervention being used to know physical and cognitive improvements in older women throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
7
0
1
Order By: Relevance
“…Therefore, in the present study data 12 participants (6 males and 6 females) from the intervention group were included in the final analysis. Based on the effect size of 0.521 previously reported for the effect of 8-week concurrent strength and aerobic Training on HR in Older Adult (Morente-Oria et al [ 33 ], the present sample size (12 participants) can allow a statistical power of 0.95 for an α value of 0.05, as calculated by G * power software (version 3.1.9.2; Kiel University, Kiel, Germany) for an ANOVA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study data 12 participants (6 males and 6 females) from the intervention group were included in the final analysis. Based on the effect size of 0.521 previously reported for the effect of 8-week concurrent strength and aerobic Training on HR in Older Adult (Morente-Oria et al [ 33 ], the present sample size (12 participants) can allow a statistical power of 0.95 for an α value of 0.05, as calculated by G * power software (version 3.1.9.2; Kiel University, Kiel, Germany) for an ANOVA.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that regular dancing training could contribute to the prevention of falls and of dementia (by stimulating neuroplasticity in certain brain regions [ 29 ]), thus fostering successful and autonomous aging. Investigating both cardiac-related output and cognitive parameters in healthy older adults, a more recent study showed that eight-weeks of concurrent training (aerobic and strength exercises) may improve aerobic capacity, operationalized by increasing maximal oxygen consumption (VO 2 max) and vigilance (related to executive functions) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy ageing is the key to maintaining an adequate level of physical performance, which is needed to be able to successfully perform everyday activities [ 24 ]. Currently, there is a large number of tests whose objective is to assess the physical condition of different population groups.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios previos con entrenamiento concurrente en adultos mayores son de al menos 8 semanas y con una frecuencia de 2-3 sesiones/semana (Agner et al, 2018;Eduardo Lusa Cadore et al, 2018;Morente-Oria et al, 2020;Neves et al, 2018;Shiotsu & Yanagita, 2018;Timmons et al, 2018), por lo que nuestro propósito fue comprobar los efectos de 5 semanas a una frecuencia mayor (5 sesiones/semana).…”
Section: Introductionunclassified